Analysis of Heavy Equipment Productivity in the Jalan Rel Kota Langsa Reconstruction Project - Rajib Muammar; Iqbal Iqbal (Unversitas Muhammadiyah Mataram, 2025)
The quality of the road produced during the reconstruction of Jalan Rel Kota Langsa is directly dependent on the materials used, the operators, and the application of heavy equipment. Errors in heavy equipment selection will lead to low productivity. This study aims to determine the productivity levels and the required duration for each piece of equipment to complete the Langsa City Road Reconstruction project. This research employs the Bina Marga method with a quantitative approach. The analysis results show that the productivity of heavy equipment for Aggregate Base Class A (LPA) work is as follows: dump trucks = 386.352 m³/day, motor graders = 617.143 m³/day, vibrator compactor rollers = 804.270 m³/day, and water tanks = 498 m³/day. For prime coat work: air compressors = 3486 m²/day and asphalt distributors = 647.089 liters/day. For Asphalt Concrete-Binder Course (AC-BC) work: dump trucks = 172.148 m³/day, asphalt finishers = 804.270 tons/day, tandem rollers = 401.017 m³/day, and pneumatic tire rollers = 365.776 m³/day. The duration required for heavy equipment execution is 2 days for LPA work, 1 day for prime coat work, and 2 days for AC-BC work.